HISTORY OF WOMEN'S EDUCATION IN BRAZIL AND PARÁ: A BRIEF STATE OF KNOWLEDGE (2019 – 2023) - de Almeida, Adriane Barbosa; Sousa, Kelly de Faro; Lobo, Thays da Silva; da Silva, Livia Sousa (Seven Editora, 2025)
The research integrates the studies of the Laboratory of Interdisciplinary Studies and Research in the History of Education and Teacher Training (LABINVE) and investigates the history of women's education between 2019 and 2023, based on dissertations and scientific initiations surveyed in three databases: BDTD, CAPES and graduate programs of public universities in Pará. The analysis highlights the absence of a consolidated subfield of the History of Women's Education, with studies often subsumed into broad categories such as gender, institutions or social movements. Based on the methodology of the state of knowledge, the study seeks to map gaps and achievements in academic production, highlighting the need for greater recognition of this subfield. Through a careful analysis, the research contributes to broadening the understanding of the historical role of women in education, proposing advances in the organization and categorization of studies in the area.DOI: https://doi.org/10.56238/sevened2024.037-142